Review Paper on Black Money in India & its Effect - Pandey, Mr. Kunthlesh Kumar (IJRDO - Journal of Applied Management Science, 2016)
Black money is not only the problem of Indian economy, but it also transcends the borders and has become a global dilemma. Recently, various studies have taken place under the Government of India to tackle the problem of black money in India. Those studies have revealed some astonishing facts about the black money market in India. In the last decade alone, India has lost approximately 125 billion in illegal money. A study has revealed that the black money even exceeds 10% of our Gross Domestic Product. This paper represents the framework, policy options and strategies that Indian Govt. should adopt to tackle with this issue and also describes the future challenges to be faced by Govt. in this context. It also studies the one of the main reason behind the generation of black money i.e. corruption. It shows up to what extent, the corruption leads to its generation which has considerable impact on various sections of the society. At last but not least, conclusion of this paper isprovided representing the ongoing issue of black money in our country and its futurecourse of action. Hopefully, this would contribute to an informed approach on thisissue as we move forward in this context